2002
DOI: 10.1006/viro.2002.1527
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HCV Structural Proteins Impairs IFN-Mediated Antiviral Response

Abstract: Hepatitis C virus (HCV), especially the genotype 1, is naturally resistant to the antiviral effects of interferon-alpha (IFN-alpha). Expression of the whole HCV genome and the NS5A protein has been suggested to interfere with the antiviral activity of IFN-alpha. Here we have analyzed the effect of individual or various combinations of HCV proteins on IFN-alpha-mediated antiviral effect against vesicular stomatitis virus (VSV). When the structural proteins (core-E1-E2) of HCV genotype 1 were expressed in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Viral protein E2 is known to inhibit PKR activities, which, in turn, might result in the attenuated antiviral effects of IFN-␣ (36). Furthermore, Keskinen et al (19) showed that expression of HCV structural proteins impaired the antiviral activities of IFNs. Thus, expression of HCV structural proteins might have compromised the anti-HCV activity of IFN-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Viral protein E2 is known to inhibit PKR activities, which, in turn, might result in the attenuated antiviral effects of IFN-␣ (36). Furthermore, Keskinen et al (19) showed that expression of HCV structural proteins impaired the antiviral activities of IFNs. Thus, expression of HCV structural proteins might have compromised the anti-HCV activity of IFN-␣.…”
Section: Discussionmentioning
confidence: 99%
“…The titer of the virus stock was 1.2 × 10 9 plaque‐forming units (PFU)/ml. Vesicular stomatis virus stocks (Indiana strain) were grown in HEp2F cells and the stock virus had a titer of 4 × 10 6 PFU/ml 10, 11. Self‐inactivating (SIN) lentivirus vector HPT‐GFP (1.4 × 10 8 infectious units (IU)/ml) (a kind gift from Professor Didier Trono, University of Geneva, Switzerland) was used in lentiviral transductions.…”
Section: Methodsmentioning
confidence: 99%
“…Vaccina virus encodes multiple genes that antagonize with the action of type I IFN (10). Also, other viruses like influenza A virus (11,12), rotavirus (13), rabies virus (14), Ebola virus (15), HSV type 1 (16), Epstein-Barr virus (17), hepatitis C virus (18)(19)(20)(21)(22), and adenovirus (23)(24)(25) have evolved means to downregulate the IFN response at different phases of infection. During retroviral infections, such as HIV, SIV, or Friend retro virus (FV), the type I IFN response is quite weak.…”
mentioning
confidence: 99%